Effects of Chitosan and 1-MCP on the Physical and Chemical Quality of Salak “Pondoh” (Salacca edulis REINW.) Fruits - Susanti, Lea; Suketi, Ketty; Kurniawati, Ani; Setyadjit (Journal of Tropical Crop Science, 2024)
Salak, or snake fruit, is a tropical fruit with a short shelf life when stored at room temperatures. The fruit’s base, if injured or bruised, can serve as an entry point for microbes, leading to physical and chemical damage to the fruits. This research aims to determine if chitosan and 1-methylcyclopropene (1-MCP) treatment can prolong the shelf life of salak “Pondoh”. The study tested two factors, chitosan (0%, 0.5%, 1.0%, 1.5%) and 1-MCP concentrations (0, 0.5, 1.0, 1.5 µL.L-1). The findings indicate that the application of chitosan and 1-MCP treatments did not significantly extend the shelf life of the fruits on the 15th day of observation. However, 1.0% chitosan combined with 1.5 µL.L-1 1-MCP and 1.5% chitosan combined with 0.5 µL.L-1 1-MCP proved effective in enhancing the fruit’s overall quality and maintained low ethylene production, high water content, and enhanced the organoleptic attributes including ease of peeling, fruit flesh color, texture, aroma, and taste.